Investigation of molecular alterations of AKT‐3 in triple‐negative breast cancer. Issue 5 (12th December 2013) - O'Hurley, Gillian; Daly, Etáin; O'Grady, Anthony; Cummins, Robert; Quinn, Cecily; Flanagan, Louise; Pierce, Aisling; Fan, Yue; Lynn, Miriam A; Rafferty, Máirín; Fitzgerald, Dara; Pontén, Fredrik; et al.
<x xml:space="preserve">Abstract</x> Aims Triple‐negative breast cancer (TNBC) is responsible for a disproportionate number of breast cancer (BC) deaths, owing to its intrinsic aggressiveness and a lack of treatment options, especially targeted therapies. Thus, there is an urgent need for the development of better targeted treatments for TNBC. Molecular alteration of AKT‐3 was previously reported in oestrogen receptor (ER)‐positive BC. AKT‐3 has also been suggested to play a role in hormone‐unresponsive BC. The aim of this study was to investigate molecular alterations of AKT‐3 in TNBC, to perform associated survival analysis, and to compare these findings with the incidence of AKT‐3 molecular alterations in ER‐positive BC. Results Our study revealed AKT‐3 amplification and deletions in 11% (9/82) and 13% (11/82) of TNBCs, respectively. In contrast, 1% (2/209) of ER‐positive BCs were found to have AKT‐3 amplifications and deletions. A higher prevalence of AKT‐3 copy number gains was observed in TNBC [26% (21/82)] than in ER‐positive BC [9% (19/209)]. AKT‐3 amplification together with Akt‐3 protein expression was negatively associated with recurrence‐free survival in TNBC. Furthermore, a negative association between high AKT‐3 copy number and recurrence‐free survival was observed. Conclusion AKT‐3 amplification could represent a potentially relevant oncogenic event in a subset of TNBCs that may, in turn, select cells sensitive to Akt‐3 inhibitors.